2015
DOI: 10.3109/13880209.2015.1075047
|View full text |Cite
|
Sign up to set email alerts
|

Saponin-enriched sea cucumber extracts exhibit an antiobesity effect through inhibition of pancreatic lipase activity and upregulation of LXR-β signaling

Abstract: (2016) Saponin-enriched sea cucumber extracts exhibit an antiobesity effect through inhibition of pancreatic lipase activity and upregulation of LXR-β signaling, Pharmaceutical Biology, 54:8, 1312-1325, DOI: 10.3109/13880209.2015 Objective: The objective of this study is to investigate the antiobesity and lipid-lowering effects of sea cucumber extracts in in vitro and in vivo models and elucidate the mechanism of action of the extracts on obesity and dyslipidemia. Materials and methods: The 60% ethanol extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
(38 reference statements)
0
22
0
1
Order By: Relevance
“… 2015 ; Guo et al. 2016 ). SREBP1 is associated with the production of an endogenous ligand that enhances PPARγ transcriptional activity and can increase the expression of several genes involved in fatty acid metabolism (Kang et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2015 ; Guo et al. 2016 ). SREBP1 is associated with the production of an endogenous ligand that enhances PPARγ transcriptional activity and can increase the expression of several genes involved in fatty acid metabolism (Kang et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown to inhibit pancreatic lipase activity under in vitro conditions [ 146 ]. Similarly, saponin extracts and echinoside A extracted from sea cucumber Pearsonothuria graeffei possess anti-obesity properties due to effective inhibition of pancreatic lipase activity and up-regulation of LXR-β signaling [ 11 ]. Taking into account all these data, it may be deduced that lipid-lowering mechanisms of sea cucumber saponins are related to inhibition of the crucial enzymes involved in lipid metabolism.…”
Section: Antihyperlipidemic Agentsmentioning
confidence: 99%
“…They have gained a lot of attention from researchers worldwide within recent decades because of their nutritive values [ 4 ] as well as their beneficial influence on human health and possible therapeutic uses. The spectrum of active compounds chemically identified from these animals is quite diverse and includes polysaccharides such as glycosaminoglycans (mucopolysacharides) including neutral glycans, fucosylated chondroitin sulfates and sulfated fucans, peptides, phospholipids and glycolipids, including glycosphingolipids (cerebrosides), polyunsaturated fatty acids, phenols, and triterpene glycosides (saponins) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In this review, the main attention is given to the compounds for which pharmacological activity has been scientifically demonstrated, physico-chemical properties required for their further standardization have been described and their mechanisms of action are more or less clear ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study found that a crude extract from the body wall (BW) of Pearsonothuria graeffei Semper (Holothuriidae) could inhibit pancreatic lipase activity and reduced total cholesterol and lipid absorptions as well as hepatic triglycerides in mice given a high-fat diet, indicating an anti-obesity effect of the extract. 7 Moreover, the sulfated triterpene saponins echinoside A (EA) and holothurin A (HA) from P. graeffei could suppress pancreatic lipase activity and increased the excretion of fatty acids in feces of mice fed with a high-fat diet. Echinoside A and holothurin A treatments also significantly decreased adipose tissue accumulation and dramatically inhibited lipid absorption in mice.…”
Section: Introductionmentioning
confidence: 99%